Polissacarídeos da biomassa do basidiomiceto Rhizoctonia solani: extração, purificação e atividade biológica - Alexandre, Samara Marrye Aguiar [UNESP] (2015)
The Rhizoctonia solani is a phytopathogenic fungus that attacks various crops, causing the tipping of seedlings. There are several studies related to the combat this microorganism, however, no reports of its biomass chemical composition. According to the literature the fungal biomass can be a promising source of molecules for the use in biological studies. Then a novel study of the chemical composition from R. solani biomass, mainly in relation to the polysaccharides, was conducted. The microorganism was grown in Vogel minimal salts medium with glucose as carbon source. Biomass resulting from various cultivations was treated consecutively with ethanol (1:20 w/v), 78 °C, 12h, 1x) and hot distilled water (1:20 w/v, 100 °C, 4h, 4x). The aqueous extract was subjected to freezing and thawing cycles in order to separate the insoluble material. The soluble fraction was precipitated in ethanol and named PEH2O (ethanolic precipitated from aqueous extract). That fraction was analyzed by GPC and the results indicated that an additional purification procedure would be necessary. Gel filtration chromatography on Sepharose CL-6B at normal pressure, separated the PEH2O in five distinct fractions named PI to PV, which eluted in decreasing order of their molecular weight. The chromatographic analysis to verify the homogeneity degree of each peak (GPC) indicated that both PIII as PV were pure and able to be chemically characterized. The results from acid hydrolysis, methylation analysis and uni- and bidimensional nuclear magnetic resonance experiments showed that PIII is a glucan with β-D-Glcp(1→3), (1→6)-linked main chain, partially substituted at O-6 by β-D-Glcp side chains and PV a fucomannogalactan with a main chain composed by (1→6)-linked -D-Galp partially substituted in O-2 by non-reducing end-units of α- L-Fucp and α-D-Manp. Some Galp units from main chain were partially methylated at OH-3. Both...